Laboratory formation and photo-chemistry of ionic HBC/anthracene clusters in the gas phase. Issue 3 (27th April 2019) - Zhen, Junfeng; Zhang, Weiwei; Yang, Yuanyuan; Zhu, Qingfeng
ABSTRACT: In this paper, we present a study of the formation and photo-chemistry of hexa-peri-hexabenzocoronene (HBC, C42 H18 )/anthracene (C14 H10 ) cluster cations in the gas phase using experimental and theoretical calculations, and we offer an approach of the evolution of carbonaceous dust grains in the interstellar medium. The experiments, which combined a quadrupole ion trap and time-of-flight mass spectrometry, show that the large cluster cations can form by gas-phase condensation through molecular-ion reactions; that is, from C14 H10 DHBC + (e.g. C14 H10 C42 H17 +, m / z  = 699), to (C14 H10 )2 DHBC + [e.g. (C14 H10 )2 C42 H16 +, m / z  = 876] and then to (C14 H10 )3 DHBC + [e.g. (C14 H10 )3 C42 H15 +, m / z  = 1053]. Furthermore, with laser irradiation, the HBC/anthracene cluster cations involve a dehydrogenation process or the loss of its mono-anthracene groups. Based on the results of experiments and quantum chemistry calculations, we demonstrate that large molecular clusters (∼100 atoms, covalently bonded) might be formed via a bottom-up process in the gas phase, and we show that there is a benefit to understanding their photo-chemical behaviour. In addition, the studies of HBC/anthracene clusters (ranging from 83 to 129 atoms or ∼2 nm in size) also provide a way of interpreting nanometre-sized grains in space.